2023
DOI: 10.1002/adfm.202212499
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic MOF‐Carbon Bridged Network Accelerates Li+‐Solvents Desolvation for High Li+ Diffusion toward Rapid Sulfur Redox Kinetics

Abstract: Lithium-sulfur batteries are famous for high energy density but prevented by shuttling effect and sluggish electrochemical conversion kinetics due to the high energy barriers of Li + transport across the electrode/electrolyte interface. Herein, the Li + -solvents dissociation kinetics is catalyzed and stimulated by designing a carbon bridged metal-organic framework (MOF@CC), aimed at realizing increased bare Li + transport for the rapid conversion kinetics of sulfur species. Theoretical simulations and spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…As summarized in Figure 3g, the Li 2 S precipitation capacity on the various DIHC shows a volcanic tendency, which is consistent with above results. For example, among them, the cell based on FeCoO 1.5 S 1.0 /NC DIHC has the earliest nucleation response time (765 s) and highest peak current (0.37 mA), showing more polysulfides were catalytically converted into Li 2 S. [46] Furthermore, the reversibility of Li 2 S has the decisive role in the later capacity and lifespan. In the Li 2 S dissolution experiment, the Li 2 S potentiostatic charge curve and capacity is recorded and summarized (Figure S20a-f…”
Section: Angewandte Chemiementioning
confidence: 99%
“…As summarized in Figure 3g, the Li 2 S precipitation capacity on the various DIHC shows a volcanic tendency, which is consistent with above results. For example, among them, the cell based on FeCoO 1.5 S 1.0 /NC DIHC has the earliest nucleation response time (765 s) and highest peak current (0.37 mA), showing more polysulfides were catalytically converted into Li 2 S. [46] Furthermore, the reversibility of Li 2 S has the decisive role in the later capacity and lifespan. In the Li 2 S dissolution experiment, the Li 2 S potentiostatic charge curve and capacity is recorded and summarized (Figure S20a-f…”
Section: Angewandte Chemiementioning
confidence: 99%
“…As summarized in Figure 3g, the Li 2 S precipitation capacity on the various DIHC shows a volcanic tendency, which is consistent with above results. For example, among them, the cell based on FeCoO 1.5 S 1.0 /NC DIHC has the earliest nucleation response time (765 s) and highest peak current (0.37 mA), showing more polysulfides were catalytically converted into Li 2 S. [46] Furthermore, the reversibility of Li 2 S has the decisive role in the later capacity and lifespan. In the Li 2 S dissolution experiment, the Li 2 S potentiostatic charge curve and capacity is recorded and summarized (Figure S20a-f DIHCs.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…For example, our group indicated that a MOF-Carbon bridged catalytic network is beneficial for promoting the formation of anion-involved Li + solvation structure, catalyzing the Li +solvents dissociation kinetics and providing a fast channel for Li + transport. [13] As pointed above, owing to the instability of MOFs and the lack of active sites, the strategy might fail in the low-temperature environments, limiting the dissociation of solvent molecules from the solvation sheath of cations, which is detrimental to the catalytic efficiency of obtaining free Li ion to propel polysulfide conversions. Therefore, designing a stable yet highly catalytic layer to accelerate the dissociation of Li + -solvents in low-temperature environment is of great significance to generate more free Li ions to facilitate sulfur redox reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%